Law, Society, and Religion: Rethinking Taʿzīr and Capital Punishment for Drug Trafficking in Indonesia - Fauzan, Muhammad Nuril (UIN Sunan Kalijaga, 2025)
This paper critically reevaluates the concept of taʿzīr—a discretionary category of punishment within Islamic criminal law—by examining its interplay with capital punishment for drug crimes in Indonesia. While taʿzīr is traditionally regarded as less severe than divinely mandated punishments such as ḥudūd and qiṣāṣ, its contemporary implementation reveals a more intricate and expansive nature. Employing Indonesia’s regulation of narcotics trafficking under Law No. 35 of 2009 (Articles 114 and 119) as a case study, the analysis contextualizes the legal framework within broader social and religious dimensions. The study demonstrates that considerations of maṣlaḥah (public interest), deterrence, and the classification of narcotics offenses as extraordinary crimes serve to legitimize the application of capital punishment. Several indicators suggest that taʿzīr may extend beyond its classical boundaries: the authorization of the death penalty for offenses not explicitly addressed in textual sources, quantitative criteria triggering maximum sanctions, reliance on state sovereignty in defining punishments, and the absence of traditional fiqh-based mitigation mechanisms. By integrating legal, societal, and religious perspectives, this study reveals that taʿzīr in the Indonesian context potentially surpass the severity of ḥudūd and qiṣāṣ punishments, thereby raising critical questions regarding the flexibility and limits of Islamic criminal justice within modern nation-states.